Transforming Rural Finance in Africa: The role of AFRACA in Linkage Banking and Financial Systems Development - Hans Dieter Seibel (Universität zu Köln, Arbeitsstelle für Entwicklungsländerforschung (AEF), 1999)
By the mid-1970s, in virtually all of Africa, strategies of modernization and technology transfer had clearly failed to initiate self-sustained processes of development. Government intervention and centralized planning had spurred economic disaster, rather than growth. In the world of finance, preferential credit had suppressed national resource mobilization and created external indebtedness without concomitant increases in productivity. In the rural economy, agricultural development banks channeled targeted credit through cooperatives and thereby undermined their potential as via ble financial intermediaries between savers and investors - borrowers. Informal finance and other indigenous self-help institutions were ignored by policy makers. Among researchers, practitioners and donor agencies, the recognition spread that a new approach was needed: one that builds on the strength of private enterprise, albeit in the informal sector, non governmental actors and the strength of indigenous human and institutional resources - to be innovatively combined with external modernization inputs.
Keywords: 330; Agrarkredit; Finanzsektor; Entwicklungsfinanzierung; Afrika